2011
DOI: 10.1080/03670244.2011.568907
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Importance of Family Solidarity, Community Structure, Information Access, and Social Capital in Predicting Nutrition Health Knowledge and Food Choices in the Philippines

Abstract: This study investigates the influence of family solidarity, community structure, information access, social capital, and socioeconomic status on the extent of nutrition and health knowledge (NHK) among primary household meal planners. In turn, we pose the question: does this knowledge influence dietary decision making? Data are taken from a survey determining socioeconomic impacts of vitamin A fortified peanut butter on Philippine households. Questions on the relationships of nutrition to health were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In their study, Moxley et al . () found that the main dietary decision maker within more cohesive families was more likely to make healthy choices, suggesting that strong family bonds can encourage their members to gain knowledge about health and learn how to take care of others. They also observed that families with strong ties are more prone to eat meals together where information and behaviours about healthy eating can be reinforced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Moxley et al . () found that the main dietary decision maker within more cohesive families was more likely to make healthy choices, suggesting that strong family bonds can encourage their members to gain knowledge about health and learn how to take care of others. They also observed that families with strong ties are more prone to eat meals together where information and behaviours about healthy eating can be reinforced.…”
Section: Resultsmentioning
confidence: 99%
“…Some of them ask whether certain activities are done in the family (yes/no answer) and others refer to the frequency. Activities here are very diverse and include, among others, sitting and talking, watching TV, going for a walk, going to a concert, going on a picnic, going to the movies, playing sports, working on a project, having birthday parties or eating meals together (Bala-Brusilow 2010, Berntsson et al 2007, Dufur et al 2013, Farrell 2010, Ferlander and Maekinen 2009, Furstenberg and Hughes 1995, Gonsalves 2007, Han 2012, Jokinen-Gordon 2007, Lau and Li 2011, Li and Delva 2012, Morgan and Haglund 2009, Morgan et al 2012, Moxley et al 2011, Rothon et al 2012, Wu et al 2010) . Morgan and Haglund (2009) did not find a significant association between family social interaction and life satisfaction in teenagers, but other studies showed a positive effect between doing joint activities with family and health-related outcomes such as overall self-reported health (Ferlander andMaekinen 2009, Morgan et al 2012), the likelihood of obesity in children (Bala-Brusilow 2010) or the consumption of fruits and vegetables (Morgan et al 2012).…”
Section: The Measurement Of Family Social Capitalmentioning
confidence: 99%
“…Civic engagement may be an additional pathway through which social capital encourages healthy eating. This can be explained by a higher sense of obligation towards oneself and to others that would eventually lead to proactive nutrition-related activities, as seen with regard to adherence to Mediterranean diet among pregnant women (71), or better nutritional habits at home when moms had higher levels of social capital (72). Our results indicate that while these mechanisms are valid in our sample too, collective efficacy should also be taken into account when conceptualizing the relationship between neighbourhood social capital and health and, more importantly, that both health-promoting and health-damaging effects need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Last, some of the studies did take behavioural intermediates into account, but as far as obesity is concerned, they almost always referred to physical activity. The link between social capital and dietary habits is a much less explored area, and studies on social capital and nutrition have been more focused on exploring how social capital can leverage people confronting food insecurity situations than on obesity‐related behaviours . It means that the little research conducted in this area has mainly been set out to know to which extent can social capital mediate the relationship between low SES and diet.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of family social capital based on a network perspective fall roughly into two categories: One, following the work by Coleman, considers marital status, the number of adults, and number of children in the household (Ferlander, Ma, Maekinen, & Ma, 2009; Furstenberg & Hughes, 1995; Helliwell & Putnam, 2004; Runyan et al, 1998), and a second separate strand developed by Litwin (2014), Litwin (2011), Litwin and Stoeckel (2014) Litwin and Shiovitz-ezra (2010), Moxley, Jicha, and Thompson (2011), Keating and Dosman (2009) and Widmer, Kempf, Sapin, and Galli-Carminati (2013) that draws upon network analyses to go deeper into the study of family ties. In youth, the main measure used has been the ratio of children/adults as an indicator of the availability of parental resources allocated within the family.…”
Section: Introductionmentioning
confidence: 99%